2000
DOI: 10.1088/0960-1317/10/2/308
|View full text |Cite
|
Sign up to set email alerts
|

Composition and structure of NiTiCu shape memory thin films

Abstract: Preliminary results on NiTiCu shape memory alloy thin-film deposition on silicon are reported. Characteristics of these films (composition, density and electrical resistivity) were correlated with working gas pressure and rf power during sputtering. The films were then annealed in order to crystallize them. The properties of these films were examined as functions of annealing and measurement temperatures in order to evidence shape memory behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…where q is the measured density of NiTiCu foam and q B is the density of bulk NiTiCu, 6.5 g/cm 3 [21]. A Skyscan1172 X-ray l-CT scanner was used to perform combined cyclic compression testing and 3D X-ray tomography.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…where q is the measured density of NiTiCu foam and q B is the density of bulk NiTiCu, 6.5 g/cm 3 [21]. A Skyscan1172 X-ray l-CT scanner was used to perform combined cyclic compression testing and 3D X-ray tomography.…”
Section: Methodsmentioning
confidence: 99%
“…Sehitoglu et al [18,19] and Biscarini et al [20] investigated the mechanical properties of NiTiCu single crystal SMAs under compression loading, and reported that the slip resistance increases when Ni-rich precipitates are present. To date, the mechanical behavior of bulk NiTiCu SMA is well established [7,[14][15][16][17][18][19][21][22][23][24]; however, few studies have focused on the effect of porosity on NiTiCu SMAs [25][26][27][28]. Goryczka et al [26,27] examined powder processing methods for producing homogenous NiTiCu SMAs.…”
Section: Introductionmentioning
confidence: 99%
“…8 However, it has been well established that sputter deposition is the most practical technique for depositing NiTi with sufficient shape memory effect. 6,[9][10][11][12][13][14][15] Sputtering is the best option for depositing NiTi thin films because the conventional vacuum evaporation of NiTi leads to the potential problem of difference in evaporation rate due to difference in vapor pressure, thus making composition control more difficult. 1 One of the techniques used for sputtering NiTi onto silicon (Si) wafers is simultaneous cosputtering from a Ni50Ti50 alloy and pure Ti targets.…”
Section: Figmentioning
confidence: 99%
“…The most important property is the resistance at high mechanical stress so these alloys are deformable and they are also biocompatibile [1][2][3][4]. In last years many papers have been written about these alloys, but little has been dedicated to thin films alloys.…”
Section: Introductionmentioning
confidence: 99%